The Effect Of Spiritual Quotient On Students’ Learning Achievement Through Students’ Learning Efforts - Nurjayanti, Nurjayanti; Deci Ririen; Susilawati Susilawati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The objective of the study was to determine the effect of spiritual quotient on students’ learning achievement through students’ learning efforts. The study used a correlational study. The participants of the study were 195 college students of Institute of Technology and Bisiness of Indragiri which was taken by using cluster sampling. The data were collected using questionnaire and was analyzed using multiple linear regression analysis. The finding showed there was no significant effect between students’ spiritual quotient on students’ learning achievement, there was a significant effect between students’ efforts on students’ learning achievement, there was no significant effect between students’ spiritual quotient on students’ learning achievement through students learning efforts.